SEMANTIC ANALYSIS OF THE VERB IN UZBEK AND RUSSIAN (World Bulletin of Social Sciences, 2023)
A verb is a word category that expresses action, state or process and has grammatical categories such as tense, aspect, declension, proportion, perfective, modality, and others. Verbs are words that mean action. In grammar, the meaning of action is very broad and includes actions, states, mental changes, biological processes, as well as similar actions and phenomena. In addition to the fact that all this has its own private parties, there is also a side that is common to all of them, that is, they are considered phenomena that occur in relation to time. The verb is an independent word category that represents an action, state or process, that is, an action such as the appearance and change of a certain character. All such meanings inherent in the verb go back to the general sense of action, which helps to distinguish it from other word categories.